Theories on Correlation between Human Capital and Economic Growth: Examining the Impact of Human Capital on Economic Growth and Financial Development (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Human capital and financial development of a country have a solid relationship. Human capital impacts financial growth and can help build an economy by broadening the kin’s knowledge and expertise. Human capital alludes to the information, skill ranges, and experience laborers have in an economy. The abilities give monetary incentive since a learned workforce can prompt expanded profitability. The idea of human capital is the recognition that not everyone has similar ranges of skills or information. Likewise, the nature of work can be improved by putting resources into individuals' training. Monetary development is an expansion in an economy's capacity, contrasted with past periods, to create merchandise and ventures. Financial development is estimated by the adjustment in the total national output (GDP) of a nation. Gross domestic product is a portrayal of the all out yield of merchandise and enterprises for an economy.